Three-dimensional patterns from the thin-film drying of amino acid solutions - Zhang, Xuehua (2015)
Experimental atomic force microscopy (AFM) images show the dried-in patterns from amino acid solutions which can be in the form of dots or networks. The three-dimensional lattice-gas Kinetic Monte Carlo (KMC) model is applied to simulate the formation of dot-like and network-like particle structures from the evaporating thin films of solutions. A sigmoidal jump in the chemical potential value is implemented to obtain dual-scale structures with the grain size distribution peaking at two distinctive values. The simulated and experimental results are qualitatively comparable.